2020
DOI: 10.1001/jamaoncol.2019.4728
|View full text |Cite
|
Sign up to set email alerts
|

Communication With Older Patients With Cancer Using Geriatric Assessment

Abstract: IMPORTANCE Older patients with cancer and their caregivers worry about the effects of cancer treatment on aging-related domains (eg, function and cognition). Quality conversations with oncologists about aging-related concerns could improve patient-centered outcomes. A geriatric assessment (GA) can capture evidence-based aging-related conditions associated with poor clinical outcomes (eg, toxic effects) for older patients with cancer. OBJECTIVE To determine whether providing a GA summary and GA-guided recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 204 publications
(130 citation statements)
references
References 68 publications
3
127
0
Order By: Relevance
“…In a nationwide cluster-randomised clinical trial including 541 older adults with metastatic cancer from 31 community oncology practices, using a geriatric assessment tool to improve age-related concerns improved patient satisfaction (p=0.04). 36 Further, the satisfaction rates were sustained over a 6-month period and remained higher in the group who received geriatric assessments compared with those who were only assessed if the patients met criteria for depression or cognitive impairment (p=0.04). 36 Additionally, caregivers in the intervention group were more satisfied (p=0.03).…”
Section: Caregiver Well-being Outcomesmentioning
confidence: 88%
See 1 more Smart Citation
“…In a nationwide cluster-randomised clinical trial including 541 older adults with metastatic cancer from 31 community oncology practices, using a geriatric assessment tool to improve age-related concerns improved patient satisfaction (p=0.04). 36 Further, the satisfaction rates were sustained over a 6-month period and remained higher in the group who received geriatric assessments compared with those who were only assessed if the patients met criteria for depression or cognitive impairment (p=0.04). 36 Additionally, caregivers in the intervention group were more satisfied (p=0.03).…”
Section: Caregiver Well-being Outcomesmentioning
confidence: 88%
“…36 Further, the satisfaction rates were sustained over a 6-month period and remained higher in the group who received geriatric assessments compared with those who were only assessed if the patients met criteria for depression or cognitive impairment (p=0.04). 36 Additionally, caregivers in the intervention group were more satisfied (p=0.03). This study showed that including an assessment at patient visits improves both patient and caregiver satisfaction with communication.…”
Section: Caregiver Well-being Outcomesmentioning
confidence: 88%
“…Each of these domains is an independent predictor of morbidity and/or mortality in the geriatric population. The comprehensive assessment can improve outcomes for older survivors by identifying areas of vulnerability in need of targeted interventions [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A geriatric assessment (GA) may serve this purpose. The GA includes an evaluation of functional status, co-morbid medical conditions, cognitive function, nutritional status, social support, and psychological state, as well as a review of medications [38]. Additionally, geriatric screening tools (i.e., G8, VES-13), instruments that assess life expectancy (i.e., ePrognosis), and predictors for risks of chemotherapy toxicity (i.e., CARG or CRASH Score) can be utilized in trials to better describe or risk-stratify this population [39][40][41].…”
Section: Capture Relevant End Points That Matter To Older Patientsmentioning
confidence: 99%